Anterior temporal lobectomy improved mood status and quality of life in Chinese patients with mesial temporal lobe epilepsy: a single-arm cohort study. Issue 4 (20th February 2023) - Lu, Song; Chu, Min; Wang, Xian; Wu, Yating; Hou, Yue; Liu, Aihua
Abstract: Background: Many studies have emphasized that selective resection of epileptic lesions in temoral lobe is associated with better preservation of cognition function; whether this applies to patients with refractory mesial temporal lobe epilepsy (MTLE) remains unknown. The objective of this study was to evaluate changes in cognitive functions, mood status, and quality of life after anterior temporal lobectomy in patients with refractory MTLE. Methods: This single-arm cohort study assessed cognitive function, mood status, and quality of life, as well as electroencephalography findings, in patients with refractory MTLE who underwent anterior temporal lobectomy at Xuanwu Hospital from January 2018 to March 2019. Pre- and post-operative characteristics were compared to evaluate the effects of surgery. Results: Anterior temporal lobectomy significantly reduced the frequencies of epileptiform discharges. The overall success rate of surgery was acceptable. Anterior temporal lobectomy did not result in significant changes in overall cognitive functions (P   >  0.05), although changes in certain domains, including visuospatial ability, executive ability, and abstract thinking, were detected. Anterior temporal lobectomy resulted in improvements in anxiety and depression symptoms and quality of life. Conclusions: Anterior temporal lobectomy reduced epileptiform discharges and incidence of post-operative seizures as well as resulted in improved mood status and quality of life without causing significant changes in cognitive function.